Advanced Signal-Amplification Strategies for Paper-Based Analytical Devices: A Comprehensive Review - Thi Xoan Hoang; Le Minh Tu Phan; Thuy Anh Thu Vo; Sungbo Cho (Biomedicines, 2021)
Paper-based analytical devices (PADs) have emerged as a promising approach to point-of-care (POC) detection applications in biomedical and clinical diagnosis owing to their advantages, including cost-effectiveness, ease of use, and rapid responses as well as for being equipment-free, disposable, and user-friendly. However, the overall sensitivity of PADs still remains weak, posing a challenge for biosensing scientists exploiting them in clinical applications. This review comprehensively summarizes the current applicable potential of PADs, focusing on total signal-amplification strategies that have been applied widely in PADs involving colorimetry, luminescence, surface-enhanced Raman scattering, photoacoustic, photothermal, and photoelectrochemical methods as well as nucleic acid-mediated PAD modifications. The advances in signal-amplification strategies in terms of signal-enhancing principles, sensitivity, and time reactions are discussed in detail to provide an overview of these approaches to using PADs in biosensing applications. Furthermore, a comparison of these methods summarizes the potential for scientists to develop superior PADs. This review serves as a useful inside look at the current progress and prospective directions in using PADs for clinical diagnostics and provides a better source of reference for further investigations, as well as innovations, in the POC diagnostics field.